Land use change impact on flood reduction capacity of lake sentani, jayapura - Koyari, Elroy; Asmaranto, Runi (International Journal of Engineering and Technology, 2018)
Flood is a natural phenomenon that occurs in certain places due to natural causes and human activities. However, the imbalance in hydrological cycle will cause the flood to do damage, both materially and non-materially. Therefore, it is important to control the occurrence and magnitude. Human activities that can cause such imbalance, one of them, is land use change. Many areas of pervious area are shifting into impervious areas, which will increase the amount of surface runoff generated. This research will cover about how land use changes over the year can influence the surface runoff generated in a certain area. This research is conducted in Sentani watershed, Jayapura, Papua, Indonesia. Calculation with the aid of ArcMap 10.1 and WinTR-20 results in around 6% changes in flood discharge in the outlet for land use in year 2007, 2010, 2012, and 2016. The reservoir capacity in reducing flood discharge is also increasing over the years.Â Â Â